2019
DOI: 10.21608/ejrs.2019.46670
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Using Natural Feed Additives on Some Reproductive and Productive Performance of Doe Rabbits.

Abstract: The present study aimed to investigate the effects of different levels of dietary supplementation of rocket (Eruca Sativa) seeds, carrot (Daucus Carota L) seeds or bay laurel (Bay laurel Nobilis L)., leaves and their mixed between them on some reproductive and productive traits, antioxidant status of doe rabbits and their offspring's, during the pregnancy and lactation periods, under the same conditions.Forty eight New Zealand White (NZW) doe rabbits about 6-7 months old (2.890-3.070 kg) were randomly allotted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
2
1
0
Order By: Relevance
“…So, the opposite influence was observed in regard to TAC, where the values were significantly (p ≤ 0.05) augmented with an addition of additive-containing three types of plant products. These results were connected with Basyony and Azoz (2017) who reported that dietary supplementation of rocket (Eruca Sativa) seeds, carrot (Daucus Carota L) seeds or bay laurel leaves (Bay laurel Nobilis L), and their mixture improved significantly the antioxidant status of doe rabbits and their offspring's, during the pregnancy and lactation periods. In addition, Casamassima, et al (2017) stated that serum levels of MDA were reduced in rabbits received a diet containing one g per kg of dried bay leaves (Laurus nobilis) in feed besides 2.5% pig fat than in rabbits fed 2.5% pig fat alone.…”
Section: Effect Of Phytogenic Feed Additives On Blood Plasma Constitusupporting
confidence: 64%
“…So, the opposite influence was observed in regard to TAC, where the values were significantly (p ≤ 0.05) augmented with an addition of additive-containing three types of plant products. These results were connected with Basyony and Azoz (2017) who reported that dietary supplementation of rocket (Eruca Sativa) seeds, carrot (Daucus Carota L) seeds or bay laurel leaves (Bay laurel Nobilis L), and their mixture improved significantly the antioxidant status of doe rabbits and their offspring's, during the pregnancy and lactation periods. In addition, Casamassima, et al (2017) stated that serum levels of MDA were reduced in rabbits received a diet containing one g per kg of dried bay leaves (Laurus nobilis) in feed besides 2.5% pig fat than in rabbits fed 2.5% pig fat alone.…”
Section: Effect Of Phytogenic Feed Additives On Blood Plasma Constitusupporting
confidence: 64%
“…Specifically, rosemary oil exhibits an effective antioxidant activity due to its containing of considerable amounts of limonene, -pinene, camphor, and (Z)-linalool oxide (Jayasena and Jo, 2014). The obtained results are in agreement with those recorded by Basyony and Azoz (2017) who reported that dietary supplementation of bay laurel leaves improved significantly the antioxidant status of doe rabbits during the pregnancy and lactation periods as well as their offsprings. Similarly, Abdel-Azeem et al (2018) showed that bay laurel leaves markedly increased seminal plasma total antioxidant capacity (TAC) for New Zealand White rabbit's bucks.…”
Section: Blood Parameterssupporting
confidence: 88%
“…The mortality rate from birth up to weaning increased significantly with the increase in ambient temperature from 19.5°C in January to 34.8°C in July and the lowest and highest mortality rate values were recorded on the 1 st week in January and on the 4 th week in July, respectively (Habeeb et al, 1999). The averages of pre-weaning mortality rates were found to be as high as 71.9% in summer and 27.3% in winter (Bassuny, 1999). During the post-weaning phase, the mortality rate was 18% in summer while no mortality was recorded during winter (Habeeb et al, 1999).…”
Section: -7-pre Weaning Mortality Ratementioning
confidence: 99%